Peran Tradisi Snap Mor dalam Pendidikan Kearifan Lokal di Papua: Perspektif Ilmu Sosial Kontemporer - Hanip, Rival; Wahyudiono, Andhika; Ruma Bay, Rudolfus (LPPM Universitas PGRI Argopuro Jember, 2025)
The gap in access to adequate education for Papuan children, where 40% of them have not received sufficient education.This indicates the need for a more contextual and locally rooted educational approach to improve the quality of education.This research aims to explore the educational potential within the Snap Mor tradition as a solution to these challenges, as well as to strengthen the cultural identity and character of the younger generation.The research methodology used is qualitative based on literature, with a focus on the analysis of relevant literature.This approach allows researchers to understand social phenomena in depth without having to collect data directly from the field.Through the analysis of documents, articles, and previous research reports, researchers can identify themes and patterns related to the Snap Mor tradition and education.The research results show that the Snap Mor tradition has significant educational value in shaping character and cultural identity.The involvement of the younger generation in Snap Mor practices can enhance cultural awareness and strengthen their emotional bonds with the community.The conclusion of this study emphasizes the importance of integrating Snap Mor values into the formal education curriculum.The recommendations produced include the need for training for teachers to understand and effectively convey materials that contain local elements.